PENGARUH MUTU PEMBELAJARAN ONLINE DAN KEPUASAN TERHADAP HASIL PEMBELAJARAN ONLINE SALES COUNTER SENIOR DI JARINGAN PT. ASTRA HONDA MOTOR - Vita Maya (Jurnal Ekonomi Manajemen dan Bisnis, 2021)
This study aims to determine the effect of the quality of online learning and learning on the learning outcomes of senior sales counters in the PT Astra Honda Motor network. The method used is a quantitative method with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that the quality of online learning has a significant effect on learning outcomes by 43.4%, hypothesis testing is obtained t count > t table or (4,748 > 1,990). learning has a significant effect on online learning outcomes by 37.4%%, hypothesis testing is obtained t count > t table or (3.623 > 1,990). Online Learning Quality and Learning Outcomes simultaneously have a significant effect on the regression equation Y = 4.089 + 0.434 X1 + 0, 374 X2 and the contribution of the influence is 64.8%, the test is obtained by F arithmetic > F table or (75.338 > 3, 11).